Multiple Intelligence in the Perspective of the Qur'an - M. Husnaini; Ahmad Syauqi Fuady; Irnie Victorynie (Indonesian Journal of Islamic Education Studies (IJIES), 2020)
This is a qualitative-descriptive analytic research aims to explore cues in the Qur'an that describe the concept of multiple intelligences. In Islam, the Qur’an is a complete guide for life. Indeed, many books that talk about multiple intelligences. However, there hasn’t been a book that specifically explain multiple intelligences according to the perspective of the Qur’an. This qualitative research used a literature review (research library)—data obtained through a literary approach in library data collection. The data were then analyzed using a thematic interpretation approach (maudhu'i). The results of this study: (1) deep linguistic intelligence-Nisa: 82, Al-Baqarah: 171, Al-An'am: 50, Ali Imran: 7; (2) Logical-mathematical intelligence in Al-Waqiah: 58-59, Al-Insan: 2, Ar-Ra'du: 3, Al-Anbiya: 30, An-Nur: 43; (3) visual-spatial intelligence in Ar-Ra'du: 3, Qaf: 7-8; (4) kinesthetic intelligence in Al-Baqarah: 219, Yasin: 68; (5) musical intelligence in Asy-Syuara: 221-227; (6) intrapersonal intelligence in Adz-Dzariyat: 21, Al-Baqarah: 44, Yasin: 62, Al-Mulk: 10; (7) interpersonal intelligence in Ar-Rum: 21, Al-Baqarah: 76, Ali Imran: 118; (8) naturalist intelligence in Al-Baqarah: 164, An-Nahl: 11, An-Nahl: 69, Al-Ghasyiyah: 17; (9) existentialist intelligence in Yunus: 24, Az-Zumar: 42, Al-Baqarah: 269. Researchers suggest educational institutions should add new insights regarding their learning strategies with multiple intelligences, especially those whose source of inspiration is the Qur'an and to other researchers should examine concept of musical intelligence, interpersonal intelligence, and naturalist intelligence perspective of the Qur’an